Analisis Dispensasi Perkawinan terhadap Anak di Bawah Umur: Studi Kasus Penetapan Pengadilan Agama Serang Nomor : 1968/Pdt.P/2020/PA.Srg - Thoby Nusabahari; Edi Mudjaidi Amin (Yustisia Tirtayasa: Jurnal Tugas Akhir, 2021)
In general, every human being has a desire to get married. It is known that within the scope of marriage, there is a marriage dispensation. Marriage dispensation is the granting of permission to enter into marriage for a prospective groom and/or bride who is not yet 19 years old. During the Covid-19 pandemic in 2020, the fact is that the number of applications for marriage dispensation at the Serang Religious Court has increased from the previous year. One of his petitions is in the case which has now been determined by the Serang Religious Court Judge, namely the Serang Religious Court Determination Number : 1968/Pdt.P/2020/PA.Srg. Departing from the court ruling above, the authors conducted an essay research by taking two problem identifications. First, is the Judge’s consideration in the Serang Religious Court Determination Number : 1968/Pdt.P/2020/PA.Srg regarding marriage dispensation in accordance with the Marriage Law in conjunction with the Marriage Age Change Law and the Child Protection Law? Second, what is the impact of giving dispensation to marriage in the Serang Religious Court Determination Number : 1968/Pdt.P/2020/PA.Srg? The research method used by the author is juridical normative, with research specifications in the form of a statutory approach and a case approach, data sources in the form of primary data and secondary data, data collection techniques in the form of library research and interviews, data analysis in the form of qualitative analysis, and research locations in the Serang Religious Court. As for the essay research conducted by the author, the result show that the Judge’s consideration in the Serang Religious Court Determination Number : 1968/Pdt.P/2020/PA.Srg regarding marriage dispensation is in accordance with the Marriage Law in conjunction with the Marriage Age Change Law and the Child Protection Law. The impact of giving marriage dispensation in the Serang Religious Court Determination Number : 1968/Pdt.P/2020/PA.Srg also varies, there are positive impacts, including being able to carry out marriages legally according to religious and state law and avoid adultery and unregistered marriage, and negative impacts, including the possibility of maternal death at a young age due to premature pregnancy, loss of adolescence, and lack of mental maturity to care for a family.